Therapeutic potential of mushrooms: a review on NF-κB modulation in chronic inflammation - Amirullah, Nur Amalina; Abdullah, Erlina; Zainal Abidin, Nurhayati; Abdullah, Noorlidah; Manickam, Sivakumar (Elsevier, 2024)
Numerous mushroom species are valued not just for their flavor but also for their health advantages. Historically, these mushrooms have been utilized for medicinal purposes across different parts of the world. Research has revealed that metabolites derived from these fungi have health benefits. Recently, there has been a growing interest in understanding how these fungal metabolites provide their healing effects and comprehend their mechanisms of action. A primary focus is the nuclear factor NF-κB, a family of transcription factors essential for regulating inflammation, cell proliferation, and apoptosis. Dysregulation and abnormal activation of NF-κB proteins are associated with a variety of diseases. Various studies have investigated mushroom compounds and their impact on various conditions, including inflammatory bowel disease, gut health, metabolic syndrome, neuroinflammation, liver injury, renal and pulmonary diseases, and autoimmune disorders. This review provides a comprehensive summary of the NF-κB signaling pathway and other related inflammatory pathways. It discusses the bioactive compounds found in mushrooms, their potential to alleviate various diseases, and the specific inflammatory pathways, particularly NF-κB, that these bioactives target.